PELATIHAN PENGGUNAAN FINANCIAL TECHNOLOGI UNTUK KETAHANAN EKONOMI - Mohammad Sigit Adi Nugraha; Faruk Sofyan, Joel; Faridha Nurazizah Yasirrahayu; Uddin, Badie; Setiawati, Popong (POLITEKNIK LP3I JAKARTA, 2025)
The community service activity with the theme of Training on the Use of Financial Technology for Economic Resilience in Karyamekar Village, Garut Regency aims to strengthen the Economic Resilience of MSMEs in Karyamekar Village, Garut, through Training on the Use of Financial Technology (FinTech). The main background is the low digital financial literacy of partners, which leads to manual cash flow management practices (cash-based) and high vulnerability to liquidity risks and informal loans. The implementation method uses a Participatory Approach and Technical Guidance (hands-on) for 25 MSMEs. The FinTech intervention focused on the QRIS application for e-payment transactions and simple e-bookkeeping software for financial recording. The evaluation results showed significant program effectiveness. There was an increase in digital financial literacy of 82.2% (the average score increased from 45 to 82), and the application adoption rate in operational simulations reached 80%. This FinTech adoption directly impacted operational efficiency improvements, reduced recapitulation time and increased cash flow transparency. The conclusions show that effective FinTech training is a realistic key to transforming the financial management of rural MSMEs, building a credible data footprint, and mitigating risks. A key recommendation is the need for support from the Garut Regional Government in providing stable digital infrastructure to ensure the program's sustainability.